Analisis Implementasi Responsive Governance Di Rumah Sakit Umum Daerah Sultan Imannudin Melalui Sultan Imannudin Dokumentasi dan Informasi Publik Online (SI DIPO) - Rizal Mustakim; Ida Hayu Dwimawanti; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
As a form of effort to improve the quality of governance, the efforts being made by the current government are through providing information disclosure to the public in accordance with the mandate of the Public Information Disclosure Act. Based on data from the 2021-2022 Public Information Openness Index, it is found that one of the areas outside Papua that has a low openness value in Central Kalimantan. Even though it is the lowest, one good practice of information disclosure is owned by Sultan Immanuddin Pangkalan Bun Hospital, through the Online Public Information Documentation Information System (SI DIPO) service. Through these data, the author seeks to research related to the responsiveness provided in terms of public information, one of which is through SI DIPO. This research was conducted using descriptive qualitative methods, with the result that RSUD already has good responsive governance from the aspects of responsiveness and innovation. However, the partnership and evaluation components are two things that need to be improved to obtain maximum service. The inhibiting factor that becomes a challenge in developing SI DIPO is online hacker attacks which need to be maximized immediately related to handling them.